New Design of A Micro-Hydro Power Plant (MHPP) System In The 3T Region As Al-ternative Solution Unit Turbine Using Computational Fluid Dynamics (CFD) Simulation - Syed Jarrar Pirzada; Intan Kurniawan; Nidia Pialina Nababan; ⁠Taufik Roni Sahroni (Eduvest - Journal of Universal Studies, 2024)
This research aims to select the most suitable type of water turbine for the micro-hydro power plant (PLTMH) site in the Anggi District, Pegunungan Arfak Regency, West Papua Province. The study also aims to design the most optimal and effective turbine in terms of technical aspects and generator system reliability. This objective is directed towards providing recommendations for the development of the second unit of PLTMH Anggi in a more comprehensive manner rather than relying solely on expert recommendations without thorough analysis. The data used in this research was obtained from field surveys and secondary data sources. The initial step in selecting the turbine type involves manual turbine design calculations, taking into consideration parameters such as water flow, head height, and hydraulic efficiency. Based on these calculation results, the "Francis" turbine type was chosen as the preferred option, differing from the existing Propeller Tubular Type-S turbine installed in Unit 1. The selected turbine, "Francis," was then modeled using computational fluid dynamics (CFD) simulations with the Ansys Fluent software. These simulations provide computer-generated data on hydrodynamic characteristics, pressure distribution, and flow velocity around the turbine under various operational conditions. This research has significant implications for improving the efficiency and reliability of the micro-hydro power plant system for the optimal power and efficiency development of Unit 2.